Hubungan Tingkat Pengetahuan Dan Sikap Perawat Tentang Pemberian Obat Terhadap Tindakan Pendokumentasian Keperawatan - Endang Epi Sri Sumarni; Gamya Tri Utami; Veny - Elita (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2014)
This research aims to determine the relationship of the level of knowledge and attitude of nurses on drug giving in nursing documentation . The design of this research was